2014
DOI: 10.14202/vetworld.2014.141-145
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic parameters of meloxicam after its oral administration in goat

Abstract: Aim:The objective of the present study was to find out the levels of analgesic drug meloxicam in the blood plasma of young goats. The drug was given to them through oral route. Data was used to elucidate the Pharmacokinetic determinants of the drug which were employed to arrive at the dose schedule and frequency of the drug in goats. Materials and Methods:Elaborate pharmacokinetic research of the drug meloxicam was done on 18 to 24 months old, five adult male local goats (Capra hircus) of Assam weighing 20 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Some information about MEL pharmacokinetics in goats and other small ruminant species is present in the literature (Shukla et al, 2007;Ingvast-Larsson et al, 2011;Wani et al, 2013;Wani et al, 2014). In the present study, the mean AUC value (26499 ± 4233 ng*hr/mL) was similar to data reported by Shukla et al, (2007Shukla et al, ( ) (19230 ± 2230 ng*hr/mL) and Ingvast-Larsson et al, (2011) (29738± 8576 ng*hr/mL) where goats received the same dose administered in the present study (0.5 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some information about MEL pharmacokinetics in goats and other small ruminant species is present in the literature (Shukla et al, 2007;Ingvast-Larsson et al, 2011;Wani et al, 2013;Wani et al, 2014). In the present study, the mean AUC value (26499 ± 4233 ng*hr/mL) was similar to data reported by Shukla et al, (2007Shukla et al, ( ) (19230 ± 2230 ng*hr/mL) and Ingvast-Larsson et al, (2011) (29738± 8576 ng*hr/mL) where goats received the same dose administered in the present study (0.5 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic profile of MEL shows good absorption, longer elimination half-life and high extravascular bioavailability in different animal species: dogs (Hare et al, 2013;Montoya et al, 2004;Busch et al, 1998), cats (Lehr et al, 2010;Giraudel et al, 2005), horses (Lees et al, 1991;Toutain and Cester, 2004;Burns et al, 2010), rabbits (Turner et al, 2006;Carpenter et al, 2009), turtles (Di Salvo et al, 2016), green iguanas (Divers et al, 2010), piglets (Alassane et al, 2010;Fosse and Spadavecchia, 2011), cattle (Johnn et al, 2011;Coetzee et al, 2009Coetzee et al, , 2012Mosher et al, 2012), camels (Wasfi et al, 2012 and Ilamas (Amanda et al, 2012). Little and conflicting information only is available for small ruminants (Shukla et al, 2007;Ingvast-Larssom et al, 2011;Wani et al, 2013;Wani et al, 2014).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Meloxicam is frequently administered orally to sheep and goats. The pharmacokinetics of meloxicam following oral administration to sheep 78 and goats [79][80][81] has been evaluated in only a limited number of studies. Currently, FARAD recommends a 15-day meat WDI following PO administration of a single dose of meloxicam (1 mg/kg) to small ruminants.…”
Section: Combined Florfenicol-flunixin Meglumine Formulation-mentioning
confidence: 99%
“…It is frequently used in domestic animals for the treatment of laminitis, mastitis, myositis, pleuritis, pneumonia, premature labor, sprain, synovitis, severe and prolonged inflammation accompanying with musculoskeletal ailments, and for managing postoperative pain. It has 12 times more selectivity in inhibiting COX-2 activity over COX-1 (Kay-Mugford et al, 2000;Wani et al, 2014). It has been shown to be a best substitute for diclofenac after ban in 2005-06 due to catastrophic decline in vulture population upto 95% in the subcontinent since 1990 (Prakash et al, 2003).…”
Section: Introductionmentioning
confidence: 99%